Digital Healthcare and Expertise Mental Health and New Knowledge Practices - Egher, Claudia (Health, Technology and Society, 2023)
"This book will be of interest to anyone who wants to know more about how expertise is multiple, dynamic and complex." - Deborah Lupton, SHARP Professor in the Centre for Social Research in Health and Social Policy Research Centre, UNSW Sydney. "Claudia Egher gives voice to the new experts of bipolar disorder, where user agency is reconciled with choice architecture and solidarity persists, as a latent and stubborn dimension of individualization and personalization." - Tamar Sharon, Professor of Philosophy, Digitalization and Society, Radboud University Nijmegen. This open access book explores how expertise about bipolar disorder is performed on American and French digital platforms by combining insights from STS, medical sociology and media studies. It addresses topical questions, including: How do different stakeholders engage with online technologies to perform expertise about bipolar disorder? How does the use of the internetfor processes of knowledge evaluation and production allow for people diagnosed with bipolar disorder to reposition themselves in relation to medical professionals? How do cultural markers shape the online performance of expertise about bipolar disorder? And what individualizing or collectivity-generating effects does the internet have in relation to the performance of expertise? Claudia Egher is a postdoctoral researcher in the department Health, Ethics and Society at the Faculty of Health, Medicine and Life Sciences of Maastricht University. Her research interests include the digitalization of (mental) healthcare, the social and cultural dimensions of emerging science and technologies, and innovative participatory practices through which citizens engage in matters of shared concern in (mental) healthcare.